2018
DOI: 10.1177/0300060518786419
|View full text |Cite
|
Sign up to set email alerts
|

Splenic artery embolization with detachable balloons for hypersplenism

Abstract: ObjectiveThis study was performed to investigate the efficacy of proximal splenic artery embolization using detachable balloons for patients with hypersplenism and portal hypertension.MethodsTwelve patients diagnosed with hypersplenism with thrombocytopenia or leukocytopenia caused by portal hypertension were treated by proximal splenic artery embolization with detachable balloons and metallic fibered coils. All patients were followed for up to 6 months. Blood parameters, coagulation factors, and liver functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…3 Many studies demonstrated that the SAE was very effective for cirrhotic patients, as shown by increased peripheral blood cell counts. [4][5][6] However, few studies focused on the severe complications after SAE. In this study, we reported 16 patients with severe post-SAE complications, and discussed their symptoms, therapies and prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many studies demonstrated that the SAE was very effective for cirrhotic patients, as shown by increased peripheral blood cell counts. [4][5][6] However, few studies focused on the severe complications after SAE. In this study, we reported 16 patients with severe post-SAE complications, and discussed their symptoms, therapies and prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Numata et al [ 54 ] reported that PSE was also effective in improving liver function status in cirrhotic patients with hypersplenism. It is found by Pang et al [ 55 ] that total bilirubin levels decreased in patients after PSE and returned to normal levels after 6 months. Hayashi et al [ 56 ] found that 1 year after PSE, patients' serum albumin and cholinesterase increased to 104 ± 14% and 130 ± 65% of pretreatment levels, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The major findings from this review included an increase in hemoglobin, leukocytes, and thrombocytes 2 4 7 8 9 11 12 13 as well as a reduction in spleen volume, 2 7 8 12 hepatic wedge venous pressure, 6 9 portal venous blood flow and portosystemic shunt pressure, 8 10 and gastroesophageal varices 2 4 6 7 9 10 after PSE. While Waguri et al 10 reported an improvement in liver function tests after PSE, Ozturk et al 11 and Pålsson et al 4 did not find a significant change.…”
Section: Resultsmentioning
confidence: 93%